Empires of Eurasia how imperial legacies shape international security - Jeffrey Mankoff (New Haven Yale University Press, 2022)
Russian Identity Between Empire and Nation -- Russia's Borderlands and the Territorialization of Identity -- Russia's Near Abroad and the Geopolitics of Empire -- Those Who Call Themselves Turks : Empire, Islam, and Nation -- On the Margins of the Nation and the State : Turkey's Kurdish Borderland -- The Geopolitics of the Post-Ottoman Space -- Iranian Identity and Iran's "Empire of the Mind" -- Iran's Borderlands : The Non-Persian Periphery -- Greater Iran (Iranzamin) and Iran's Imperial Imagination -- Civilization and Imperial Identity in China -- China's Inner Asian Borderlands -- Sinocentrism and the Geopolitics of Tianxia -- A World Safe for Empire?
Keywords: Imperialism--History.